GC–FID determination of tetramethylpyrazine and acetoin in vinegars and quantifying the dependence of tetramethylpyrazine on acetoin and ammonium. (15th January 2018) - Xiao, Zijun; Zhao, Ling; Tian, Li; Wang, Linhui; Zhao, Jing-yi
Highlights: A simple and accurate GC method was developed for determination of tetramethylpyrazine and acetoin in vinegars. Tetramethylpyrazine in vinegars follows second-order polynomial models of acetoin and ammonium concentrations. Acetoin and ammonium were deduced to be the precursors of TMP in vinegars by isotopic tracing. Abstract: 2, 3, 5, 6-Tetramethylpyrazine (TMP) is an important health functional composition in vinegars, but there are controversial viewpoints about its formation mechanism and scarce relevant records on TMP content enhancement in vinegar products. In this study, a simple and accurate solvent extraction coupled with GC–FID method was developed for the simultaneous determination of TMP and acetoin in vinegars and 137 worldwide samples were analyzed. Meanwhile, the ammonium contents of all the vinegar samples were determined using the salicylate method. By nonlinear surface fitting, the concentrations of TMP in vinegars were found to follow second-order polynomial models of acetoin and ammonium concentrations. By isotopic tracing using 13 C labelled acetoin and 15 N ammonium, acetoin and ammonium were deduced to be the precursors of TMP in vinegars.